2009
DOI: 10.1002/ejic.200900050
|View full text |Cite
|
Sign up to set email alerts
|

Gas‐Phase Model Studies Relevant to the Decomposition of Transition‐Metal Nitrates M(NO3)2 (M = Co, Ni) into Metal–Oxo Species

Abstract: Electrospray ionization (ESI) of aqueous cobalt(II) and nickel-(II) nitrate solutions inter alia affords the solvated, mono-and oligonuclear nitrato complexes [M m + (M = Co, Ni; m = 1-5; n = 1-4). The collision-induced dissociation spectra of the mass-selected ions imply that these ions correspond to genuine hydrated metal(II) nitrato complexes in that either cluster degradation through expulsion of neutral M(NO 3 ) 2 or sequential loss of water ligands take place. In the case of the lowest member of the ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
29
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 85 publications
3
29
0
Order By: Relevance
“…The type of fragmentation reaction depends on the oxidation state of the metal. The Cu(NO 3 ) 3 − cluster showed loss of NO 3 • but no loss of NO 2 • , whereas the Cu(NO 3 ) 2 − cluster showed loss of NO 2…”
mentioning
confidence: 84%
See 3 more Smart Citations
“…The type of fragmentation reaction depends on the oxidation state of the metal. The Cu(NO 3 ) 3 − cluster showed loss of NO 3 • but no loss of NO 2 • , whereas the Cu(NO 3 ) 2 − cluster showed loss of NO 2…”
mentioning
confidence: 84%
“…2 These experiments were recently reinvestigated by Franśki et al using quadrupole time-of-flight (TOF) mass spectrometer for collision-induced dissociation (CID). 1 Both studies reported the loss of NO 3 − , NO 3 • , and NO 2 • as the primary decomposition pathways for many transition metal nitrate cluster anions. Specific reactions varied depending on the charge of the metal.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…The decomposition of gas-phase metal nitrate anions, M(NO 3 ) n − , can result in the elimination of neutral NO 2 , producing MO(NO 3 ) n−1 − . [12][13][14] In cases where higher oxidation states of the metal are accessible than that in the nitrate precursor, oxidation of the metal center can occur during these processes. would similarly comprise Pu(VII).…”
Section: Introductionmentioning
confidence: 99%